Experimental study on yarn pullout test of shear thickening fluids natural fibres fabric - Muhammad Syaiful Amri Abd. Rahman (Universiti Teknologi Malaysia, 2025)
This study describes the process behaviour of woven fabrics to yarn pull-out in relation to their mechanical properties. The main purpose of the research is to investigate the relationship between the effects of Shear Thickening Fluids (STF) impregnated fabric and the yarn pull-out behaviour, followed with a detailed comparison of maximum friction force between the fabric fibres in static and dynamic stage. The main particle composition of STF solution is consist of fumed silica as dispersing particle and polyethylene glycol (PEG400) as dispersing medium was prepared to impregnating with the fabric. Besides, the fabric were made of from different type of fibre which is Pineapple, Jute, Basalt, and Glass fibre. Samples are tested in three categories which is neat fabric and STF-treated fabric with two type concentration of STF (15, 20 wt% of fumed silica). Based on the previous study, the presence of STF will increases the friction between warp and weft yarns, as well as prevents yarns from moving freely. During the experiment, the pull-out test has been performed at velocity of 50 mm/min. Result of the experiment show that the maximum friction force increase after being treated with STF compare to neat fabric and the force is getting higher along with the increasing in the concentration of STF. Result of the experiment were compare with STF/Kevlar from previous study to identify the ability of the sample. Comparing the yarn pull-out values shows that the maximum value of the STF-treated samples is higher than neat fabric without affecting the fabric flexibility.